2016
DOI: 10.1016/j.ijscr.2016.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous flexor tendon rupture due to an insufficiency fracture of the hamate hook in a patient with systemic lupus erythematosus: A case report

Abstract: HighlightsWe report a case of spontaneous flexor tendon rupture in a patient with SLE.Nonunion of the hamate hook is one of the causes of flexor tendon rupture.SLE patients have an increased risk for osteoporosis and insufficiency fractures.Tenosynovitis and long-term steroid use can affect tendon integrity in SLE.SLE can lead to both tendon degeneration and insufficiency fracture of the hamate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In Melamed’s case [ 11 ], as bilateral multiple renal artery microaneurysms consistent with PAN diagnosis, the patient received methylprednisolone 1 g daily for three days followed by oral prednisone 60 mg daily and a pulse of intravenous cyclophosphamide 1000 mg. However, if the ruptured place was constituted of connective tissue, such as the junction between the renal pelvis and kidney [ 7 ], steroids were reduced or stopped to encourage healing due to the reason that glucocorticoids have a catabolic effect on connective tissue, muscle, fat, skin and wound healing [ 26 ]. In our case, the patient presented with high disease activity; after the resolution of the bleeding and restoration of hemodynamic stability, she was given intravenous pulses of methylprednisolone and had an uneventful recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In Melamed’s case [ 11 ], as bilateral multiple renal artery microaneurysms consistent with PAN diagnosis, the patient received methylprednisolone 1 g daily for three days followed by oral prednisone 60 mg daily and a pulse of intravenous cyclophosphamide 1000 mg. However, if the ruptured place was constituted of connective tissue, such as the junction between the renal pelvis and kidney [ 7 ], steroids were reduced or stopped to encourage healing due to the reason that glucocorticoids have a catabolic effect on connective tissue, muscle, fat, skin and wound healing [ 26 ]. In our case, the patient presented with high disease activity; after the resolution of the bleeding and restoration of hemodynamic stability, she was given intravenous pulses of methylprednisolone and had an uneventful recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published case report, El Ouazi et al showed the value of US and MRI in the diagnosis of bilateral patellar tendon rupture in a patient with SLE [ 50 ]. Hosokawa et al highlighted the case and the imaging findings of a SLE patient with spontaneous rupture of the flexor tendon of the little finger [ 51 ].…”
Section: Sle Arthropathymentioning
confidence: 99%
“… 2 Tendon rupture is a serious complication; its rarity has limited study of incidence to case reports. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…2 Tendon rupture is a serious complication; its rarity has limited study of incidence to case reports. 3,4 Hamate fractures can be classified using the Milch classification into fractures of either the body or hook. Fractures of the hook are typically associated with sporting activity that involves direct force onto or across the hook of hamate, such as baseball, golf, and racquet sports.…”
Section: Introductionmentioning
confidence: 99%